Synthesis and Preliminary Evaluation of an F-18 Labeled Fluoropyridine Losartan Analog as a Novel PET Tracer for Imaging AT1 Receptors - Arksey, Natasha C. (Université d'Ottawa / University of Ottawa, 2012)
Several cardiac diseases, including hypertrophy, cardiomyopathy, and myocardial infarction, result in the upregulation of cardiac angiotensin II type-1 receptors (AT1R). Imaging the AT1R in vivo via PET provides the potential to monitor disease progression and guide therapy accordingly. The aim of this research was to develop a novel F-18 labeled losartan analog as an AT1R PET tracer and begin evaluation in rats. Due to the longer half-life and shorter positron range of F-18, we presume that an F-18 labeled tracer will be more beneficial than current C-11 labeled tracers. Prior structure-activity relationship (SAR) studies suggested the addition of substituents to the hydroxyl group of losartan would minimally affect AT1R binding affinity. [18F]Fluoropyridine losartan ([18F]FPyrLos) was synthesized in an automated module through conjugation of [18F]fluoro-3-pent-4-yn-1-yloxypyridine ([18F]FPyKYNE) to azide-modified losartan via the Cu(I)-catalyzed azide-alkyne 1,3-dipolar cycloaddition (CuAAC) ‘click’ reaction. [18F]FPyrLos was produced in approximately 10% yield (decay-corrected) with > 97.5% purity and specific activities up to 4,200 mCi/µmol. MicroPET (Siemens Inveon) images of normal Sprague Dawley rats displayed high uptake in the kidneys (ratio of 8.3 compared to surrounding tissue at 10 min). Metabolite analysis in the kidneys and plasma by column-switch HPLC revealed that roughly two-thirds of the tracer was unchanged 10 min post-injection and that one labeled hydrophilic metabolite exists, accounting for roughly 6% of the total activity. Both microPET and metabolism studies displayed a dose-dependent reduction in renal uptake upon co-injection with AT1R blocker candesartan indicating specific binding. Further work in rat disease models is required to evaluate the potential of this tracer for imaging cardiac AT1R.
Keywords: AT1R; F-18; AngII; PET